1998
DOI: 10.1146/annurev.fluid.30.1.443
|View full text |Cite
|
Sign up to set email alerts
|

Air-Water Gas Exchange

Abstract: ▪ Abstract  The exchange of inert and sparingly soluble gases—including carbon dioxide, methane, and oxygen—between the atmosphere and oceans is controlled by a thin 20- to 200-μm-thick boundary layer at the top of the ocean. The hydrodynamics in this layer are significantly different from boundary layers at rigid walls, since the orbital motion of the waves is of the same order as the velocities in the viscous boundary layer. Laboratory and field measurements show that wind waves significantly increase the ga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
190
1
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 281 publications
(203 citation statements)
references
References 53 publications
11
190
1
1
Order By: Relevance
“…water activity 0.95 13 Formic, acetic, propionic and butyric acids; indoles and phenols 20 ; methyl-, ethyl-, propyl-, butyl-, amyl-, isobutyl-, iso-amyl-, hexyl-, dipropyl-and dibutyl-amine 12 ; indole and phenols 6 Eubacterium 11,2,21,8,10, ; Anaerobic conditions 20 Formic, acetic, propionic, butyric; iso-butyric, valeric, caproic, iso-valeric and iso-caproic acids; indoles and phenols 20 ;2,14,18 Some strains are obligate anaerobes 14 Butyric acid and other short chain fatty acids 14 19 ;8 3, ; Oxygen tolerant 20 ; facultative anaerobe 7 Formic, acetic, propionic and butyric acids; ammonia and volatile amines 20 ; methyl-, ethyl-, propyl-, butyl-, amyl-, iso-butyl-, iso-amyl-, hexyl-, dipropyl-and dibutyl-amine 12 Supporting Information S4 -Detailed discussion of the diffusion and emission of odorants from porous media S4.1. Molecular diffusion and boundary theories Diffusion and transport of gases from liquid and porous media are complex and dynamic processes that have previously been described or reviewed by Capelli et al (2012), , Jähne and Haußecker (1998), Parker et al (2010), , Thibodeaux and Scott (1985) and Zhang et al (2002). Molecules of a compound move randomly within a medium (e.g.…”
Section: S25 Odour Threshold Values For Individual Odorantsmentioning
confidence: 99%
“…water activity 0.95 13 Formic, acetic, propionic and butyric acids; indoles and phenols 20 ; methyl-, ethyl-, propyl-, butyl-, amyl-, isobutyl-, iso-amyl-, hexyl-, dipropyl-and dibutyl-amine 12 ; indole and phenols 6 Eubacterium 11,2,21,8,10, ; Anaerobic conditions 20 Formic, acetic, propionic, butyric; iso-butyric, valeric, caproic, iso-valeric and iso-caproic acids; indoles and phenols 20 ;2,14,18 Some strains are obligate anaerobes 14 Butyric acid and other short chain fatty acids 14 19 ;8 3, ; Oxygen tolerant 20 ; facultative anaerobe 7 Formic, acetic, propionic and butyric acids; ammonia and volatile amines 20 ; methyl-, ethyl-, propyl-, butyl-, amyl-, iso-butyl-, iso-amyl-, hexyl-, dipropyl-and dibutyl-amine 12 Supporting Information S4 -Detailed discussion of the diffusion and emission of odorants from porous media S4.1. Molecular diffusion and boundary theories Diffusion and transport of gases from liquid and porous media are complex and dynamic processes that have previously been described or reviewed by Capelli et al (2012), , Jähne and Haußecker (1998), Parker et al (2010), , Thibodeaux and Scott (1985) and Zhang et al (2002). Molecules of a compound move randomly within a medium (e.g.…”
Section: S25 Odour Threshold Values For Individual Odorantsmentioning
confidence: 99%
“…Compared with the cases with free-slip boundary conditions at the surface, the transfer velocity reduces significantly when using no-slip boundary conditions. Assuming that the transfer velocity scales with the Schmidt number according to the power law K L ∝ Sc n , Davies (1972) and Jähne & Haussecker (1998) have shown that the power n changes from −1/2 for a mobile (clean) interface to −2/3 for a solid-wall (severely contaminated) interface. This scaling is confirmed in figure 12 where the interpolating line of the free-slip data points has a slope of −1/2, while for the no-slip cases, the slope obtained for the range between Sc = 2 and Sc = 500 was −2/3.…”
Section: Concentration and Mass Flux Profilesmentioning
confidence: 99%
“…In the case of severe contamination, hydrodynamically the gas-liquid interface behaves like a solid-liquid interface. As a result, the exponential dependency of K L on Sc, in contrast to the conceptual models above, changes from −1/2 for a clean interface to −2/3 for a severely contaminated surface (see Davies 1972;Jähne & Haussecker 1998;Hasegawa & Kasagi 2008). In agreement with the conceptual models above, for clean surfaces the dependency of K L on Sc −1/2 was confirmed in the parametric study of Herlina & Wissink (2014), who carried out DNS calculations in which gas transport equations for various Sc between 2 and 500 were solved using exactly the same background turbulent flow field.…”
mentioning
confidence: 98%
“…[52] Gas-transfer velocities at the air-sea interface have been studied; see Jähne and Haußecker [1998] for a review. The instantaneous and local gas-transfer velocities of wind waves have been estimated using an infrared imaging technique, the so-called controlled flux technique (CFT), which is based on relations among heat transfer rates, gastransfer velocities, and Schmidt numbers [Haußecker et al, 1995].…”
Section: Turbulent Thermal Diffusion On the Surfacementioning
confidence: 99%